Influence of CYP2C9 genetic polymorphisms in the PK/PD study of naproxen in saliva samples by LC MS/MS - Oliveira, Gabriela de Moraes (2022)
Individual responses to non-steroidal anti-inflammatory drugs (NSAIDs) are influenced by a combination of pharmacokinetic and pharmacodynamic factors (PK/PD) that may be under the regulatory influence of some genetic factors, which is the path for personalizing the prescription today, with satisfactory efficacy and minimal side effects. Polymorphisms in CYP2C9 can significantly interfere with the PK and PD parameters of non-steroidal anti-inflammatory drugs (NSAIDs), including naproxen. The synthesis of prostaglandin E2 (PGE2) is modulated by the enzyme cyclooxygenase-2 (COX-2) and changes in PGE2 can be used to quantify the inhibition of COX-2 after the administration of NSAIDs, which is a good target for investigation. The present research aimed to study the PK/PD parameters of naproxen and its metabolite, 6-O-desmethylnaproxen, associated with allelic variations of CYP2C9. In our study, a fast, selective and sensitive method of liquid chromatography coupled to mass spectrometry (LC-MS/MS) was developed and validated, according to ANVISA standards, for the determination of naproxen, its main metabolite, 6- O-desmethylnaproxen and PGE2 in saliva. Saliva collections (4 mL) were sequential in times: before and 0.25; 0.5; 0.75; 1; 1.5; two; 3; 4; 5; 6; 8; 11; 24; 48; 72 and 96 h after taking a naproxen tablet (500 mg). The PGE2 analysis proved to be effective and sensitive for the analysis of PD parameters. Both naproxen and its main metabolite, 6-O-desmethylnaproxen, and PGE2 in saliva can be effectively quantified using LC-MS/MS following an oral dose of naproxen. Our method proved to be effective and sensitive to determine the lower limit of quantification of naproxen, its metabolite, 6-O-desmethylnaproxen, and PGE2 in saliva (2.4 ng/mL). All validation data, such as accuracy, precision, and intra- and inter-assay repeatability, were less than 15%. Allelic variations of CYP2C9 may be considered relevant in the pharmacokinetics of naproxen, its main metabolite, 6-0-desmethylnaproxen and PGE2.